Characteristics of children with severe preschool asthma prior to starting the TIPP study - Zielen, S.; Wosniok, J.; Wollscheid, N.; Nickolay, T.; Grimmel, C.; Scheele, D.; Sattler, F.; Prenzel, F.; Lorenz, M.; Schaub, B.; Lex, C.; Dahlheim, M.; et al. (Frontiers in Pediatrics, 2025)
ObjectiveChildren with preschool asthma suffer disproportionally more often from severe asthma exacerbations with emergency visits and hospital admissions than school children. However, there are only a few reports on characteristics, hospitalization, phenotypes and symptoms in this age cohort.Patients and methodsThis analysis of an ongoing prospective trial of Tiotropium bromide in preventing severe asthma exacerbations (the TIPP study) assessed baseline characteristics, hospitalizations and symptoms in 100 children with severe preschool asthma. Children aged 1–5 years were analyzed at study enrollment and daily symptoms were recorded by an electronic diary [Pediatric Asthma Caregiver Diary (PACD)] for the following four weeks until randomization.ResultsAt enrollment, the total number of severe asthma exacerbations, defined as three days systemic steroid use or hospitalization in the last 24 months, was mean (±SD) 5.8 ± 5.7 and the test for respiratory and asthma control in kids (TRACK) was mean 46.9 ± 19.0. Daily recording of symptoms by the PACD revealed that only 7 patients were controlled at randomization, whereas 35 were partially and 58 were uncontrolled according to GINA.ConclusionDespite protective therapy with inhaled corticosteroids (ICS), most children of this severe asthma cohort were only partially or uncontrolled according to GINA guidelines.